Tantangan dan Peluang Generasi Z dalam Pengelolaan Sumber Daya Alam di Masa Depan - Adik Ayu; Neza Aini Ariyanto; Wardatun Nikmah; Nurus Sobakh (Indo Publishing, 2026)
Natural resource management is an important aspect in achieving sustainable development to ensure human welfare both in the present and future generations. Generation Z, as a digital-native generation, has significant potential in managing natural resources innovatively and adaptively. This research aims to analyze the challenges and opportunities faced by Generation Z in natural resource management. This study uses a qualitative approach using a literature review method, with data collected from books, scientific journals, and academic publications. The findings reveal that Generation Z faces several challenges, including a consumptive lifestyle and low environmental awareness. In addition, the overexploitation of natural resources remains a major problem contributing to environmental degradation. However, Generation Z also has considerable opportunities through the use of digital technology and environmental innovation. Therefore, Generation Z plays an important role as agents of change in promoting sustainable management of natural resources through technological advances and increased environmental awareness.